Determining the shortest path on an intuitionistic fuzzy graph with interval value using floyd Warshall algorithm - Rakhmawati, Nahlia; Widodo, Agus; Hidayat, Noor; Alghifari, Abdul Rouf (AIP conference proceedings, 2022)
The shortest path problem is a classical network optimization problem which has a wide range of applications in various fields. One of the interesting algorithms to solve shortest path problem is Floyd Warshall s algorithm. The advantage of the floyd warshall algorithm is that it’s capability to obtain the shortest distance between all edges on the graph. In this study, the Floyd Warhsall algorithm is applied to shortest path on an interval-valued intuitionistic fuzzy graph. Intuitionistic fuzzy graph is a graph with an intuitionistic fuzzy number value that is used to describe the relationship between each vertices. It was the firstly used of Floyd Warshall algorithm in an interval-valued intuitionistic fuzzy graph. Here we examined the effectiveness of the Floyd Warshall algorithm by comparing it with the results of previous studies.